REPRESENTASI PEREMPUAN DALAM MEME MEDIA SOSIAL: PERSPEKTIF FEMINISME SIMONE DE BEAUVOIR TERHADAP STEREOTIP GENDER - Safitri, M.Pd., Nur Anita Syamsi; Humaira, Annisa Nur Afiat (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2025)
This study aims to analyze the representation of women in social media memes through the lens of Simone de Beauvoir’s existentialist feminism. In the digital context, memes function not only as entertainment but also as a medium for disseminating ideology also gender stereotypes that often disadvantage women. This study employs a qualitative method with a descriptive approach. The material objects are memes circulating on social media, while the formal object is Beauvoir's feminist concept that positions women as autonomous subjects rather than "the Other." The analysis focuses on visual and textual elements within memes to uncover the forms of gender stereotypes being reproduced. The findings reveal that women are frequently represented in subordinate roles, tied to domestic responsibilities, and judged based on unfair patriarchal standards. These representations reinforce male dominance and constrain women's freedom as independent subjects. The results highlight the need for critical awareness in consuming and producing digital content, as well as the importance of deconstructing gender stereotypes within digital popular culture.